Advanced microelectromechanical systems-based nanomechanical testing: Beyond stress and strain measurements. (11th June 2019) - Bhowmick, Sanjit; Espinosa, Horacio; Jungjohann, Katherine; Pardoen, Thomas; Pierron, Olivier
Abstract: Abstract : The field of in situ nanomechanics is greatly benefiting from microelectromechanical systems (MEMS) technology and integrated microscale testing machines that can measure a wide range of mechanical properties at nanometer scales, while characterizing the damage or microstructure evolution in electron microscopes. This article focuses on the latest advances in MEMS-based nanomechanical testing techniques that go beyond stress and strain measurements under typical monotonic loadings. Specifically, recent advances in MEMS testing machines now enable probing key mechanical properties of nanomaterials related to fracture, fatigue, and wear. Tensile properties can be measured without instabilities or at high strain rates, and signature parameters such as activation volume can be obtained. Opportunities for environmental in situ nanomechanics enabled by MEMS technology are also discussed.